Context-Aware Trails - CLARKE, SIOBHAN (My University, 2004)
he emergence of converged mobile devices with a wide range of computing, communications, entertainment, and sensing capabilities represents a major step in the evolution of wireless computing. Such devices increasingly shift the decision-making power from the user to the machine, which has the capacity to be better informed about the current environment and can respond more quickly
PUBLISHED
Keywords: Computer Science